Urine Klotho Is Lower in Critically Ill Patients With Versus Without Acute Kidney Injury and Associates With Major Adverse Kidney Events - Neyra, Javier A. (Crit Care Explor, 2019)
Klotho and fibroblast growth factor-23 were recently postulated as candidate biomarkers and/or therapeutic targets in acute kidney injury. We examined whether urine Klotho and serum intact fibroblast growth factor-23 levels were differentially and independently associated with major adverse kidney events in critically ill patients with and without acute kidney injury. DESIGN: Single-center, prospective, case-control study. SETTING: ICU in a tertiary medical center. PATIENTS: Fifty-four acute kidney injury patients and 52 controls without acute kidney injury admitted to the ICU. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Acute kidney injury was defined by Kidney Disease: Improving Global Outcomes criteria and included only acute kidney injury stage greater than or equal to 2. Controls were matched by age, gender, and baseline estimated glomerular filtration rate. Paired serum and urine samples were obtained 24–48 hours after acute kidney injury diagnosis (cases) or ICU admission (controls). The primary outcome was 90-day major adverse kidney events, which was the composite of all-cause death, dependence on renal replacement therapy, or a 50% or higher decrease in estimated glomerular filtration rate from baseline. Major adverse kidney events, which was the composite of all-cause death, dependence on renal replacement therapy, or a 50% or higher decrease in estimated glomerular filtration rate from baseline. Major adverse kidney events developed in 44 patients (41.5%). Patients in whom major adverse kidney events developed had more comorbidity, higher acuity of illness scores, and more prevalent acute kidney injury. Levels of urine Klotho adjusted by creatinine were lower, and serum intact fibroblast growth factor-23 levels were higher in acute kidney injury patients versus ICU controls. In adjusted models, the highest versus lowest tertile of urine Klotho/creatinine was independently associated with an overall 95% lower risk of major adverse kidney events (81% lower risk in patients with acute kidney injury). The highest versus lowest tertile of serum intact fibroblast growth factor-23 was associated with more than 300% higher risk of major adverse kidney events. CONCLUSIONS: Urine Klotho/creatinine levels were significantly lower and serum intact fibroblast growth factor-23 levels were significantly higher in critically ill patients with acute kidney injury versus matched controls without acute kidney injury. When measured in the first 48 hours of ICU admission or acute kidney injury diagnosis, urine Klotho/creatinine independently associated with major adverse kidney events, particularly in patients with acute kidney injury. These results show promise for testing these biomarkers—individually or in combination—as part of novel risk prediction models of renal outcomes in the ICU.